The challenges of establishing Digital Library services in an Open Distance Learning (ODL) / Zubaydah Zamri and Norazleen Mohamad Noor - Zamri, Zubaydah; Mohamad Noor, Norazleen (2020)
The Digital Library services has play an important role in establish in an Open Distance Learning (ODL). Digital library has a large number of learning instructional data such as text, video and audio to adjust compatibility to the distance learners. The distance learners can accessible 24/7 to the information and with the same resources allowing to use simultaneously by a number of institution at one-time usage. The Digital Revolution has affected nearly every aspect of library and museum services, from the automation of internal recordkeeping systems to the digitization of physical collections, and from the acquisition of new "born-digital" works of art or library publications to the use of technology to present collections and engage audiences. Distance learners are connected and accessible anywhere as long as an internet connection is available by using the technological devices such tablet, smartphone or personal PC. The above analysis of a definition will be the basis of the next section. If we take as an example the definition: "A digital library is an online system that stores media assets, and provides services for retrieving and presenting this content to humans or other online systems" then, the "digital library" is called the definiendum; Online system is the genus; Stores media assets and provides services are the differentiae. This study provides useful information on Digital Library Services about the challenges and how to help the development of e-learning methods among the ODL learners. Methodology term that researcher using for gathering data analysis and forecast is using the survey technique. A qualitative method will also be conducted via observation and interviews through the participants who are among the ODL learners from the university selected.